2017
DOI: 10.1590/1980-5373-mr-2016-0478
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Effect on Structural and Optical Properties of ZnO Thin Films Deposited by RF Magnetron Sputtering

Abstract: ZnO thin films with wurtzite structure have been grown on Si (100) and glass substrates using radio frequency (rf) magnetron sputtering at room temperature. The ZnO thin films have been characterised by XRD. The (002) orientation is observed at zero Oxygen flow after the (100) developed with increasing oxygen ratio. Usually, this orientation (100) is difficult to obtain. The thickness of ZnO films was confirmed by cross-section SEM, and their stoichiometry was measured by Energy Dispersive X-ray Spectroscopy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
32
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 87 publications
(43 citation statements)
references
References 36 publications
3
32
1
1
Order By: Relevance
“…200 nm, prepared by thermal oxidation) [25] compared to native films (several nanometers thin) under droplets of zinc sulfate. [30][31][32][33][34][35][36][37][38] To the best of our knowledge, no synthesis of dense nanogranular ZnO layers using "one-step" sputtering (with no annealing post-treatment) has been reported before. In contrast, Thomas et al evidenced a protective effect of ZnO patinas grown under artificial seawater droplets.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…200 nm, prepared by thermal oxidation) [25] compared to native films (several nanometers thin) under droplets of zinc sulfate. [30][31][32][33][34][35][36][37][38] To the best of our knowledge, no synthesis of dense nanogranular ZnO layers using "one-step" sputtering (with no annealing post-treatment) has been reported before. In contrast, Thomas et al evidenced a protective effect of ZnO patinas grown under artificial seawater droplets.…”
Section: Introductionmentioning
confidence: 99%
“…The authors suggested a greater ability of the thick layers to reduce oxidizing species (such as O 2 molecules). [36][37][38] There seems to be a trend indicating that, when the O 2 partial pressure is increased, more randomly-oriented grains are observed in XRD experiments. [26] The patinas exhibited a significant gradient of porosity with an open structure on the electrolyte side and a compact one close to the zinc substrate.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations